Nations and personalities - BEER, Amy-Jane; Peter Mitchell; Amy Jane Beer (New York : Chelsea House, 2006)
Provides introductory information about African geography and culture. Each of the first five volumes covers a region within the continent (North, West, southern, East, and Central Africa); the sixth volume (titled Nations and personalities) provides details on each African country and continent-wide international organizations.
Includes index, further resources
Adult
Keywords: Terminology Civilization Ethnology Africa